MANAJEMEN PEMBERDAYAAN EKONOMI BERBASIS PONDOK PESANTREN: STUDI DI PONDOK PESANTREN DARUL QUR’AN AT-TAQWA DDI JAMPUE KABUPATEN PINRANG - Heriyani, Heriyani; Putra, Trisno Wardy; Masse, Rahman Ambo (Investama : Jurnal Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze how to plan, implement and supervise economic empowerment at the Darul Qur'an At-Taqwa DDI Jampue Islamic boarding school, Pinrang Regency. The type of research used is qualitative using a phenomenological approach. The sources of research data are boarding school leaders and Islamic boarding school business managers. Furthermore, the data collection methods used were observation, interviews and documentation. Then there are three stages of data management and analysis techniques: data collection, data processing, and drawing conclusions. The results of this research indicate that currently the Darul Qur'an At-Taqwa Ddi Jampue Islamic boarding school, Pinrang Regency, is not yet effective in carrying out its economic empowerment management. Planning for economic empowerment has not been well structured, including in terms of determining tasks and responsibilities, as well as clarity of vision and mission, however at the implementation stage economic activities in Islamic boarding schools have gone well, although the funds obtained are still not able to fully support Islamic boarding school empowerment. Supervision at this cottage has been carried out quite well, they have formed a supervisory team and hold regular meetings. The implications of this research are: a) For the Islamic boarding school and business managers of the Darul Qur'an At-Taqwa DDI Jampue Islamic boarding school, Pinrang Regency, they can explore further the business potential that can be developed in their area to provide opportunities for all students in the Islamic boarding school. . For santri and female students to be more active and enthusiastic in the economic empowerment process, because financial skills training is an added value that can be obtained from Islamic boarding schools.